Motion and structure estimation from stereo image sequences - Weng, J.; Cohen, P.; Rebibo, N. (IEEE transactions on robotics and automation, 1992)
A closed-form approximate matrix-weighted solution for estimating motion parameters from point correspondences in two stereo image pairs is presented. The corresponding algorithm is noniterative and fast. Simulation shows that the solution is significantly more reliable than the unweighted and the scalar-weighted solutions, except when the number of point correspondences is less than seven. The matrix-weighted least squares solution can be used as a final solution if the speed requirement does not allow iterations. An approach to optimal estimation of the motion parameters and the structure of the three-dimensional points is also introduced. In experiments with a calibrated real stereo setup, the motion parameters and depth maps were automatically computed from real-world images. Some ground truths were used to validate the accuracy of these results.< >